Dicranopteris linearis extract inhibits the proliferation of human breast cancer cell line (MDA-MB-231) via induction of S-phase arrest and apoptosis - Baharuddin, Aifaa Akmal; Roosli, Rushduddin Al Jufri; Zakaria, Zainul Amiruddin; Md Tohid, Siti Farah (Taylor & Francis, 2018)
Context: Dicranopteris linearis (Burm.f.) Underw. (Gleicheniaceae) has been scientifically proven to exert various pharmacological activities. Nevertheless, its anti-proliferative potential has not been extensively investigated. Objective: To investigate the anti-proliferative potential of D. linearis leaves and determine possible mechanistic pathways. Materials and methods: MTT assay was used to determine the cytotoxic effects of D. linearis methanol (MEDL) and petroleum ether (PEEDL) extracts at concentrations of 100, 50, 25, 12.5, 6.25 and 3.125 µg/mL against a panel of cancer cell lines (breast [MCF-7 and MDA-MB-231], cervical [HeLa], colon [HT-29], hepatocellular [HepG2] and lung [A549]), as compared to negative (untreated) and positive [5-fluorouracil (5-FU)-treated] control groups. Mouse fibroblast cells (3T3) were used as normal cells. The mode of cell death was examined using morphological analysis via acridine orange (AO) and propidium iodide (PI) double staining. Cell cycle arrest was determined using flow cytometer, followed by annexin V-PI apoptosis detection kit. Results: MEDL demonstrated the most significant growth inhibition against MDA-MB-231 cells (IC50 22.4 µg/mL). PEEDL showed no cytotoxic effect. Induction of apoptosis by MEDL was evidenced via morphological analysis and acridine orange propidium iodide staining. MEDL could induce S phase cell cycle arrest after 72 h of incubation. Early apoptosis induction in MDA-MB-231 cells was confirmed by annexin V-FITC and PI staining. Significant increase in apoptotic cells were detected after 24 h of treatment with 15.07% cells underwent apoptosis, and the amount escalated to 18.24% with prolonged 48 h incubation. Conclusions: MEDL has potential as a potent cytotoxic agent against MDA-MB-231 adenocarcinoma.